Enhancing Ecotourism Through Inclusive Language: A Case Study of Lon Malang Beach, East Java - Kurniawan, Bima; Rosyadi ZA, Dede; Imam Romadlani, M. Masqotul (e-Journal of Linguistics; Vol 20 No 1 (2026): ejl-January, 2025)
This research examines the strategic role of inclusive language in promoting Lon Malang Beach as an ecotourism destination in Sampang Regency, East Java. Despite its high ecotourism potential in terms of natural beauty and rich local culture, this one of northern beach in Madura island remains relatively unknown, among Generation Z in particular. Employing a descriptive qualitative approach, this research combines field observations, in-depth interviews with stakeholders, and a survey of 150 university students to analyze the effectiveness of inclusive language in enhancing the destination's appeal and visibility. The findings reveal that 69.3% of respondents were unaware of Lon Malang Beach, primarily due to limited digital promotional strategies. Inclusive language—as defined in this study through the use of shared linguistic codes and accommodative communication strategies—has proven to play a significant role in reducing stereotypes against the Madurese community, reinforcing local cultural narratives, and encouraging tourist engagement across diverse backgrounds. Moreover, inclusive language supports equitable marketing practices by ensuring information accessibility for vulnerable groups, including persons with disabilities. This research underlines that inclusive communication approaches can build a positive and relational image of the destination through personalized and engaging language use. The findings highlight the urgency of inclusive language management within the framework of sustainable rural tourism development, addressing not only economic dimensions, but also social and cultural cohesion.